La exigencia del requisito de estar al día en el pago de la pensión alimentaria en el proceso de exoneración de alimentos y la vulneración al derecho a la tutela jurisdiccional efectiva - Farge Begazo, Johan Guiusseppi (2020)
The purpose of this legal article is to demonstrate how to be required in an absolute manner and without establishing parameters, or exceptions to compliance with the special requirement contained in article 565-A of the TUO of the Civil Procedure Code, that is, "to demonstrate to be up to date in the payment of alimony ”, whoever wants the court to extinguish a maintenance obligation to which they are obliged, violates their right to effective judicial protection, for the purposes of developing the issue it will be established that they are understood as a right to judicial protection effective and the regulatory framework in which it is developed, it will also be taken into account that it is understood by the right to food and who is obliged to grant it, and then carry out a specific analysis of the specific causes on which the claim can be sustained. of exemption of alimony, which are established in article 483 of the Civil Code, as are the s following; due to the material inability to continue fulfilling said obligation on the part of the obligor, in such a way that demanding such fulfillment puts his own subsistence at risk; for having disappeared the state of need of the obligee and finally when the obligee reaches the age of majority. Once each specific cause has been established, the parameters or exceptions for the application of said special requirement will be established at the time of qualifying the claim, and the judge must in any case via diffuse control, make the right to effective judicial protection prevail against a formal requirement that limits access to the defendants even a statement on the merits after carrying out a judicial process where the minimum guarantees are met to verify and establish on the foundations of the claim.